Persia and the Golden Rule - Harry J. Gensler (Religious Inquiries, 2013)
My paper has two parts. First, I talk about the golden rule. After introducing the rule and its global importance, I explain why many scholars dismiss it as a vague proverb that leads to absurdities when we try to formulate it clearly. I defend the golden rule against such objections. Second, I talk about the golden rule in Persia and Islam; I consider Persian sources (Muslim and non-Muslim) and also non-Persian Muslim sources. I show that the golden rule is deeply rooted in Persia and Islam. And I point out special ways that this tradition’s understanding of the golden rule can contribute to those outside this tradition.